2020
DOI: 10.1111/jcmm.16043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking‐assisted screening reveals tannic acid as a natural protein disulphide isomerase inhibitor with antiplatelet and antithrombotic activities

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…The ligands were energy-reduced before being transferred to PDBQT file format along with the protein. According to the dimensions of the protein’s active site, as determined by Discovery Studio 2021 Client, the grid box was placed in the protein to identify the binding spot for the ligands to interact or dock [ 34 ]. The grid box’s dimensions were 25 × 25 × 25, and its centre was located at X = 9.54, Y = 43.27, and Z = 63.47.…”
Section: Methodsmentioning
confidence: 99%
“…The ligands were energy-reduced before being transferred to PDBQT file format along with the protein. According to the dimensions of the protein’s active site, as determined by Discovery Studio 2021 Client, the grid box was placed in the protein to identify the binding spot for the ligands to interact or dock [ 34 ]. The grid box’s dimensions were 25 × 25 × 25, and its centre was located at X = 9.54, Y = 43.27, and Z = 63.47.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously reported that myricetin strongly inhibits arachidonic acid-evoked platelet aggregation [60] without affecting cyclooxygenase activity in platelets [60]. We decided to consider PDI, an enzyme that participates in the αIIbβ3 activation necessary for platelet activation and aggregation processes, a potential target for the flavonoid effect [61]. Myricetin, possibly due to non-covalent bonds, can bind to thiol isomerases and inhibits the reductase activity of PDI and endoplasmic reticulum (ER)-resident protein 57 (ERp57).…”
Section: Protein Disulfide Isomerasementioning
confidence: 99%
“…Punicalagin was also shown to inhibit ERp57 at low micromolar concentrations in a cell-free environment, while the biological actions of this polyphenolic compound were lost in ERp57-silenced neuroblatoma cells, suggesting ERp57 to be the main target of punicalagin in cellular systems 143 . Similarly, tannic acid was demonstrated to bind to PDI with high affinity, after a directed in silico screening of over 60 natural compounds 144 . This study demonstrated that tannic acid inhibits several thiol isomerases and prevents thrombus formation in the cremaster laser-induced model of thrombosis in vivo 144 .…”
Section: Flavonoids and Natural Compoundsmentioning
confidence: 99%
“…Similarly, tannic acid was demonstrated to bind to PDI with high affinity, after a directed in silico screening of over 60 natural compounds 144 . This study demonstrated that tannic acid inhibits several thiol isomerases and prevents thrombus formation in the cremaster laser-induced model of thrombosis in vivo 144 . Therefore, several natural compounds have been identified as potent inhibitors of PDI and other thiol isomerases, with implications to thrombosis and haemostasis.…”
Section: Flavonoids and Natural Compoundsmentioning
confidence: 99%